Activation of Epithelial-Mesenchymal Transition and Altered β-Catenin Signaling in a Novel Indian Colorectal Carcinoma Cell Line - Mylavarapu, Sanghamitra; Kumar, Harsh; Kumari, Smita; Sravanthi, L. S.; Jain, Misti; Basu, Aninda; Biswas, Manjusha; Mylavarapu, Sivaram V. S.; Das, Asmita; Roy, Monideepa (Frontiers in Oncology, 2019)
Colorectal cancer is the third major cause of cancer-related mortality worldwide. The upward trend in incidence and mortality rates, poor sensitivity to conventional therapies and a dearth of early diagnostic parameters pose a huge challenge in the management of colorectal cancer in India. Due to the high level of genetic diversity present in the Indian population, unraveling the genetic contributions toward pathogenesis is key for understanding the etiology of colorectal cancer and in reversing this trend. We have established a novel cell line, MBC02, from an Indian colorectal cancer patient and have carried out extensive molecular characterization to unravel the pathological alterations in this cell line. In-depth molecular analysis of MBC02 revealed suppression of E-cadherin expression, concomitant with overexpression of EMT related molecules, which manifested in the form of highly migratory and invasive cells. Loss of membrane-tethered E-cadherin released β-catenin from the adherens junction resulting in its cytoplasmic and nuclear accumulation and consequently, upregulation of c-Myc. MBC02 also showed dramatic transcriptional upregulation of β-catenin. Remarkably, we observed significantly elevated proteasome activity that perhaps co-evolved to compensate for the unnaturally high mRNA level of β-catenin to regulate the increased protein load. In addition, there was substantial misregulation of other clinically relevant signaling pathways that have clinical relevance in the pathogenesis of colorectal cancer. Our findings pave the way toward understanding the molecular differences that could define pathogenesis in cancers originating in the Indian population.